Stunning of Livestock before Slaughter and Modern Fiqh Research - Nabil Ahmad; Haroon ur Rasheed (Journal of Islamic and Religious Studies, 2017)
Stunning is the process of rendering animals immobile or unconscious, with or without killing the animal, when or immediately prior to slaughtering them for food. In modern slaughterhouses a variety of stunning methods are used on livestock. Methods include: Electrical stunning, Gas stunning, Percussive stunning. There are three opinions of Islamic scholars about stunning. Those scholars; who do not allow stunning at all; are of the view that the method of rendering animals unconscious before slaughter is against the shairah method and Sunnah, and it is Makrooh e Teḥreemi. Before slaughtering, if an animal died due to stunning, then that animal is carcass and is not allowed to be eaten. But, if before slaughter, ḥayat e Mustaqirrah is present in animal and it is slaughtered in that condition then it is permissible to eat it. Certain scholars allow stunning in certain situations with some terms and conditions. The decisions of Mjam e Faqhiyyah of modern age are also based on conditional permission. Moreover, Mufti Muḥammad Taqi Usmani, Dr. Wahabah Zoḥaili and Abdul Aziz Bin Baaz agree with conditional permission, while some other scholars allow all types of stunning without any condition; Mufti Muḥammad Abduho and his pupil Allamah Rasheed Raza Miṣri agree with later opinion.